NanoBubbles project: Data Management Plan - Bordignon, Frédérique (HAL (Le Centre pour la Communication Scientifique Directe), 2021)
This document is the DMP for the NanoBubbles project (ERC Synergy Grant). The project focuses on how, when and why science fails to correct itself. To understand how the correction of science works or fails, the NanoBubbles project combines approaches from the natural sciences, engineering (natural language processing) and humanities and social sciences (linguistics, sociology, philosophy and history of science). See https://nanobubbles.hypotheses.org for more information.